2011
DOI: 10.4103/0971-6580.84265
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of Ocimum Sanctum on meloxicam induced toxicity in wistar rats

Abstract: An ameliorating effect of Ocimum sanctum on the toxic effect of meloxicam, a new non-steroidal anti-inflammatory drug was studied by evaluating haemato-biochemical parameters, oxidative stress, gross and histopathological changes in various organs of Wistar rats. A total of thirty-six male rats were divided in six experimental groups each comprising of six rats and numbered from G1 to G6. Meloxicam toxicity was induced by oral feeding of meloxicam at 1.2 mg/kg and 2.4 mg/kg body weight in G2 and G3 respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Thus, tulsi has been shown to protect against the toxic effects of industrial chemicals such as butylparaben,[ 16 ] carbon tetrachloride,[ 17 ] copper sulfate[ 18 ] and ethanol,[ 19 ] and common pesticides such as rogor,[ 20 ] chlorpyrifos,[ 21 ] endosulfan[ 22 ] and lindane. [ 23 ] Tulsi has also been shown to protect against the toxic effects of many pharmaceuticals drugs including acetaminophen,[ 24 ] meloxicam,[ 25 ] paracetamol,[ 26 ] haloperidol[ 27 ] and anti-tubercular drugs. [ 28 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, tulsi has been shown to protect against the toxic effects of industrial chemicals such as butylparaben,[ 16 ] carbon tetrachloride,[ 17 ] copper sulfate[ 18 ] and ethanol,[ 19 ] and common pesticides such as rogor,[ 20 ] chlorpyrifos,[ 21 ] endosulfan[ 22 ] and lindane. [ 23 ] Tulsi has also been shown to protect against the toxic effects of many pharmaceuticals drugs including acetaminophen,[ 24 ] meloxicam,[ 25 ] paracetamol,[ 26 ] haloperidol[ 27 ] and anti-tubercular drugs. [ 28 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 110 111 ] Tulsi has also been shown to have anti-ulcer and ulcer-healing activity that has been observed in many different animal models including aspirin-, indomethacin-, alcohol-, histamine-, reserpine-, serotonin-, acetic acid-, meloxicam-, cold restraint-, pyloric ligation- and stress-induced ulceration models. [ 25 112 113 114 ] This anti-ulcer activity is attributed to multiple actions including the reduction of offensive factors such as acid-pepsin secretion and lipid peroxidation and the enhancement of gastric defensive factors such as mucin secretion, cellular mucus and longevity of mucosal cells. [ 114 115 ]…”
Section: Introductionmentioning
confidence: 99%
“…significantly decreased the concentration of GSH and the mean values were 331.03±1.49 and 323.53±1.49 µmol /ml of blood respectively. Mahaprabhu et al (2011) suggested that metabolism of meloxicam residues, generate free radicals and contribute to an increase in oxidative stress, promoting inhibition of cellular enzymes by the reduction in glutathione peroxidase (GSHPx). In agreement with that GSH concentration was significantly lower in meloxicam treatment compared to control group in present study.…”
Section: Gsh (Reduced Glutathione)mentioning
confidence: 99%
“…It produces its effect by inhibiting cylooxygenase (COX) enzyme which is found in two isoforms i.e COX-1 and COX-2. Meloxicam is selective for COX-2 than COX-1 in lower doses, but in higher doses it can inhibit COX-1 enzyme also and produces serious adverse effects (Mahaprabhu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation